Paths to more effective environmental awareness in Itabira-MG: Strengthening resilience to pandemics (Research, Society and Development, 2022)
The damage caused by rapid urban expansion, often poorly planned, can have an extremely unfavorable impact on the quality of life of the population and the environment, with direct impacts on the atmospheric environment, an essential element to life. The city of Itabira in Minas Gerais has an economy strongly linked to mining activities and particulate material is one of the main air pollutants resulting from these activities. Recent studies have shown that the COVID-19 pandemic can be potentiated in an environment with high levels of air pollution. Thus, the present study aims to analyze the relationship between particulate matter and the number of confirmed cases and deaths due to the COVID-19 pandemic in the municipality of Itabira-MG. For this purpose, epidemiological data obtained from the Health Department of Minas Gerais and the Healthy Cities Program and air quality data obtained from the Automatic Air Quality Monitoring Network of Itabira were used. Simple regression analysis showed that particulate matter explained 20% of the variability in cases of contamination and 21% of deaths by the new coronavirus. Based on the principles of sustainable development, it is concluded that a re-discussion on the relationship between human beings and nature is necessary, prioritizing actions that integrate local government, the public and private sector, and the population with the objective of improving quality of everyone's life so that future epidemics can be avoided.